2017
DOI: 10.17140/drmtoj-2-125
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Aspect of Black African Adult Women With Facial Dermatosis

Abstract: During the 5 years, we registered 7,898 patients over 18-years-old, 1,192 of these were affected by facial dermatosis that is 15.09%. The mean age was 37.7 ranging from 18 to 89-years-old. There were at least two facial dermatosis in 2.51% cases. The pigmentary disorders occurred mostly in 24.7% followed by acne group and seborrheic dermatitis (19.5%). The first three facial dermatosis of women were exogenous ochronosis, seborrheic dermatitis and lichen planus respectively 16.7%, 10.7% and 10%. Conclusion: Pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…6 Isidore et al carried out a study on facial dermatoses over a period of five years. 7 During this period a total of 7898 cases were seen who were above the age of 18 years. Out of these 7898 cases seen, the incidence of facial dermatoses was 15.1% in their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Isidore et al carried out a study on facial dermatoses over a period of five years. 7 During this period a total of 7898 cases were seen who were above the age of 18 years. Out of these 7898 cases seen, the incidence of facial dermatoses was 15.1% in their study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that pigmentory lesions were common in their study due to depigmentaiton practices prevalent in their study area cases. 7 Georgieva et al carried out a follow up study on 52 cases of facial dermatoses. 8 They tried to evaluate the quality of life associated with facial dermatoses among these patients before and after treatment.…”
Section: Discussionmentioning
confidence: 99%